Supplementary Figure S3 from Comprehensive Genome Profiling in Patients With Metastatic Non–Small Cell Lung Cancer: The Precision Medicine Phase II Randomized SAFIR02-Lung/IFCT 1301 Trial - Fabrice Barlesi (15045504) (2025)
Supplementary Figure 3. Forest plot with subgroup analysis for OS in substudy 1.